Ok so I feel stupid asking this but i am having a problem at a certain point in the problem:
If x+y=a and x-y=b then 2xy= ?
The answer is: 2xy= (a^2 - b^2)/2
I got it to this:
y= [2a/2] - [(a+b)/2]
why is the numerator then in the next step: 2a-a-b and not 2a-a+b?
hardaway, when you post the question, you don't need to post page number and problem number from OG. Just copy the question w/ all the choices.
To answer your question.(x+y)^2 = x^2 + 2xy + y^2(x-y)^2 = x^2 - 2xy + y^2
we know that:a^2 = (x+y)^2b^2 = (x-y)^2
so,a^2 - b^2 = (x^2 + 2xy + y^2) - (x^2 - 2xy + y^2)= x^2 - x^2 + 2xy + 2xy + y^2 - y^2= 4xy4xy = a^2 - b^22xy = (a^2 - b^2)/2